Interplay of RhoA and mechanical forces in collective cell migration driven by leader cells - Reffay, M.; Parrini, M. C.; Cochet-Escartin, O.; Ladoux, Benoit; Buguin, A.; Coscoy, S.; Amblard, F.; Camonis, J.; Silberzan, P. (Nature Cell Biology, 2014)
The leading front of a collectively migrating epithelium often destabilizes into multicellular migration fingers where a cell initially similar to the others becomes a leader cell while its neighbours do not alter. The determinants of these leader cells include mechanical and biochemical cues, often under the control of small GTPases. However, an accurate dynamic cartography of both mechanical and biochemical activities remains to be established. Here, by mapping the mechanical traction forces exerted on the surface by MDCK migration fingers, we show that these structures are mechanical global entities with the leader cells exerting a large traction force. Moreover, the spatial distribution of RhoA differential activity at the basal plane strikingly mirrors this force cartography. We propose that RhoA controls the development of these fingers through mechanical cues: the leader cell drags the structure and the peripheral pluricellular acto-myosin cable prevents the initiation of new leader cells. © 2014 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2024-02-19